Investigation of the cytotoxic activity of two novel digitoxigenin analogues on H460 lung cancer cells. Issue 5 (June 2020) - Boff, Laurita; Persich, Lara; Brambila, Paula; Ottoni, Flaviano Melo; Munkert, Jennifer; Ramos, Gabriela Silva; Soares Viana, Adhônis Rodrigues; Kreis, Wolfgang; Braga, Fernão Castro; Alves, Ricardo José; Maia de Pádua, Rodrigo; Schneider, Naira Fernanda Zanchett; et al.
Abstract : Cardiac glycosides (CGs) are natural compounds traditionally used for the treatment of heart disorders, and recently new therapeutic possibilities were proposed. Their antitumor reports and clinical trials have notably enhanced, including those targeted for lung cancer, the most lethal type that lacks of new treatment agents, instigating the research of these molecules. The CGs studied here, named C10 3β-[(N-(2-hydroxyethyl)aminoacetyl]amino-3-deoxydigitoxigenin and C18 (3β-(aminoacetyl)amino-3-deoxydigitoxigenin), are semisynthetic derivatives prepared from digitoxigenin scaffold. Both compounds demonstrated high cytotoxicity for different cancer cell lines, especially H460 lung cancer cells, and their cytotoxic effects were deeply investigated using different methodological approaches. C10 induced cell death at lower concentrations and during shorter periods of treatment than C18, and increased the number of small and irregular nuclei, which are characteristics of apoptosis. This type of cell death was confirmed by caspase-3/7 assay. Both compounds reduced H460 cells proliferative potential by long-term action, and C10 showed the strongest potential. Moreover, these compounds induced a significant decrease of the area and viability of H460 spheroids providing preclinical favorable profiles to develop new chemotherapeutic agents. Abstract : Supplemental Digital Content is available in the text.